Modeling and Simulation of Small Scale Microgrid System - khamis, alias (2012)
A microgrid systems is a new technology for improving reliability and providing alternative energy supplies to the grid system. Low voltage faults in the system are one of the critical issues that require distributed generating sources to disconnect from grid provide energy to the load. Therefore the techniques used in the microgrid system with microsoures can be important in reducing the problems in the grid system. In this paper two different microsources photovoltaic (PV) and wind turbine (WT) with battery storage for a small scale microgrid system are simulated. The aim is to observe the effect of microsources parameter on the outputs at the point of common coupling. Most of the results can be used for develop a small scale microgrid system for practical applications.